NAMA-update - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The Network of Agricultural Mechanization in Africa (NAMA), which was described in Spore 44 page 13, has now become fully operational. Its objective is firstly to acquire, process, and disseminate information on agricultural mechanization projects...